2021
DOI: 10.1080/19420862.2021.1914883
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumoral activity of the Pan-HER (Sym013) antibody mixture in gemcitabine-resistant pancreatic cancer models

Abstract: Chemoresistance, particularly to gemcitabine, is a major challenge in pancreatic cancer. The epidermal growth factor receptor (EGFR) and human epidermal growth factor receptors 2 and 3 (HER2, HER3) are expressed in many tumors, and they are relevant therapeutic targets due to their synergistic interaction to promote tumor aggressiveness and therapeutic resistance. Cocktails of antibodies directed against different targets are a promising strategy to overcome these processes. Here, we found by immunohistochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…For the anti-EGFR/HER2 BsAb, we employed the variable domain sequences of pertuzumab (anti-HER2) ( 27 ) and duligotuzumab/DL11 (anti-EGFR/HER3) ( 28 ). Previous studies have shown that simultaneous targeting of EGFR, HER2, and HER3 with multispecific antibodies can prevent compensatory tumor promoting mechanisms within the HER family, providing a scientific rationale for the development of a pan-HER antibody ( 29 ). For the anti-CD20/CD20 BsAb, we used the variable domain amino acid sequences from the type I anti-CD20 monoclonal antibody, rituximab ( 30 ), and a type II anti-CD20 monoclonal antibody, obinutuzumab ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the anti-EGFR/HER2 BsAb, we employed the variable domain sequences of pertuzumab (anti-HER2) ( 27 ) and duligotuzumab/DL11 (anti-EGFR/HER3) ( 28 ). Previous studies have shown that simultaneous targeting of EGFR, HER2, and HER3 with multispecific antibodies can prevent compensatory tumor promoting mechanisms within the HER family, providing a scientific rationale for the development of a pan-HER antibody ( 29 ). For the anti-CD20/CD20 BsAb, we used the variable domain amino acid sequences from the type I anti-CD20 monoclonal antibody, rituximab ( 30 ), and a type II anti-CD20 monoclonal antibody, obinutuzumab ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…The BxPC3, Sw1990, AsPC-1, and CFPAC pancreatic cancer cell lines and the SKBR3 breast cancer cell line were from ATCC (Rockville, MD) and were cultured following the ATCC recommendations. The two PDXs (P4604 and P2846) were generated from resected hepatic and peritoneum metastatic samples, respectively, from two patients with pancreatic cancer treated with gemcitabine (P4604) or untreated at surgery time (P2846) (PDX Platform, Institut de Recherche en Cancérologie de Montpellier) ( 58 ). The PDX cell line C-PDX P4604 was derived from the PDX P4604.…”
Section: Methodsmentioning
confidence: 99%
“…Sym013 was tested in vivo and in vitro against an extensive panel of more than 100 cancer cell lines and in most cases was effective [156]. It is worth mentioning that Sym013 effectively inhibited growth of models resistant to chemotherapy and HERtargeted therapies (e.g., cetuximab, trastuzumab and T-DM1) [156][157][158][159][160]. The combination of Sym013 with single or fractionated radiation in NSCLC and HNSCC xenografts, including cetuximab resistant models, showed a potent antitumor effect and delayed regrowth [158].…”
Section: Lumretuzumabmentioning
confidence: 99%